Stabilization in Discrete Nonlinear Systems Using Lyapunov Exponent - Fengjun Tang; Rong Yuan (Mathematics and Computer Science: Contemporary Developments Vol. 1, 2024)
We deal with the stabilization problem of discrete nonlinear systems. We construct a control Lyapunov function on discrete nonlinear systems. Then, we present a new method to construct a continuous state feedback law.